COLLABORATION ONLINE: SLOAN-C RESOURCES - Moore, Janet C. (Online Learning, 2006)
Over the years, insights about ALN collaboration from Sloan-C’s annual publications in the quality series, in Effective Practices, and in The Journal of Asynchronous Learning Networks (JALN), have been useful for refining theoretical and practical knowledge about online education. This summary points to additional resources related to collaboration.